Effect Of Combination Ultrasonic And Ball Milling Techniques Of Fillers Dispersion On Mechanical And Pgysical Properties Of Natural Rubber Latex Films - Hamran, Noramirah (2018)
The addition of commercial fillers like calcium carbonate, titanium dioxide, kaolin, carbon black and silica in Natural Rubber (NR) latex compounds has reduced the mechanical properties of NR latex films due to the destabilization effect in the NR latex compounds which govern by the dispersion quality, particle size and also the pH of the dispersion itself. The ball milling methods were a conventional method of preparation of dispersions and ultrasonic method has successfully used in preparation of nano fillers such as carbon nano tube (CNT). In this study, ball milling parameters (duration, speed), effect of ultrasonic parameters (duration, speed, and concentration), and combination methods were carried out. The combination of ultrasonic and ball milling methods has shown the reduction in particle size of the resulted fillers dispersion. The particle size analyzer, transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analysis were carried out to investigate the properties of fillers dispersions. The tensile and tear test were also carried out to investigate the mechanical properties of the NR latex films. The CaCO3 and TiO2 dispersions were used to investigate the effect of filler loading (0, 5, 10, 15 and 20 phr) in NR latex films. Based on the mechanical properties results, the optimum filler loading obtained was at 10 phr. The dispersion of CaCO3 was used in NR latex cleaning compound to improve the effectiveness to pull out the dirt during cleaning process. Overall, this study has specified suitable fillers dispersion preparation methods to obtain small particle size of fillers which compatible with the size of NR latex particles.